Muße-Diskurse Russland im 18. und 19. Jahrhundert - Cheauré, Elisabeth (Mohr Siebeck, 2019)
The literary discourses of this volume on »Muße«, »dosug«, and »prazdnost'« (leisure) open up new perspectives on the development of Russian culture in the eighteenth and nineteenth centuries by means of lexical and semantic approaches, and by probing philosophical, production-aesthetic and socio-historical aspects. In four comprehensive essays emanating from the Slavic studies division of the joint project SFB 1015 »Muße« and its international co-operations, questions of how transferable the phenomenon of »Muße« is to Russian literature and culture are investigated. Discursive processes of the assessment and re-evaluation of work, laziness and leisure can act as indicators for gauging societal processes as much as the condoning or discrediting of »Muße«. Besides the history of mentalities, aesthetic developments and, in particular, the emergence of new literary genres are also included.